The Spectrum of Antimicrobial Activity of Cyadox against Pathogens Collected from Pigs, Chicken, and Fish in China - Maan, Muhammad Kashif (Antibiotics (Basel), 2021)
Cyadox has potential use as an antimicrobial agent in animals. However, its pharmacodynamic properties have not been systematically studied yet. In this study, the in vitro antibacterial activities of cyadox were assayed, and the antibacterial efficacy of cyadox against facultative anaerobes was also determined under anaerobic conditions. It was shown that Clostridium perfringens and Pasteurella multocida (MIC = 0.25 and 1 μg/mL) from pigs, Campylobacter jejuni and Pasteurella multocida from poultry, E. coli, Streptococcus spp., and Flavobacterium columnare from fish were highly susceptible to cyadox (MIC= 1 and 8 μg/mL). However, F. columnare has no killing effect for drug tolerance. Under in vitro anaerobic conditions, the antibacterial activity of cyadox against most facultative anaerobes was considerably enhanced Under anaerobic conditions for the facultative anaerobes, susceptible bacteria were P. multocida, Aeromonas spp. (including A. hydrophila, A. veronii, A. jandaei, A. caviae, and A. sobria, excluding A. punctata), E. coli, Salmonella spp. (including S. choleraesui, S. typhimurium, and S. pullorum), Proteus mirabilis, Vibrio fluvialis, Yersinia ruckeri, Erysipelothrix, Acinetobacter baumannii, and Streptococcus agalactiae (MICs were 0.25~8 μg/mL, MBCs were 1–64 μg/mL). Intermediate bacteria were Enterococcus spp. (including E. faecalis and E. faecium), Yersinia enterocolitica, and Streptococcus spp. (MICs mainly were 8~32 μg/mL, MBCs were 16~128 μg/mL). This study firstly showed that cyadox had strong antibacterial activity and had the potential to be used as a single drug in the treatment of bacterial infectious diseases.